2018
DOI: 10.31014/aior.1993.01.01.7
|View full text |Cite
|
Sign up to set email alerts
|

E-Books to Enhance College Learners’ English Self-Efficacy

Abstract: The Education Quarterly Reviews is an Open Access publication. It may be read, copied and distributed free of charge according to the conditions of the Creative Commons Attribution 4.0 International license. The Asian Institute of Research Education Quarterly Reviews is a peer-reviewed International Journal. The journal covers scholarly articles in the fields of education, linguistics, literature, educational theory, research, and methodologies, curriculum, elementary and secondary education, higher education,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The results of previous findings found that the use of comic-style picture storybooks affected increasing student self-efficacy (Sipahutar, 2020). Other research states that there is an effect of using digital picture storybooks on students' self-efficacy (Chen, 2022;Yang, 2018). With increased self-efficacy, students will automatically participate in learning.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results of previous findings found that the use of comic-style picture storybooks affected increasing student self-efficacy (Sipahutar, 2020). Other research states that there is an effect of using digital picture storybooks on students' self-efficacy (Chen, 2022;Yang, 2018). With increased self-efficacy, students will automatically participate in learning.…”
Section: Discussionmentioning
confidence: 93%
“…With increased self-efficacy, students will automatically participate in learning. The use of pop-up book learning media involves students directly and provides opportunities for students to actively participate in the learning process (Damayanti et al, 2021;Yang, 2018). A collection of texts in the form of stories with pictures will give positive messages to children and impress children so that they are properly implemented for elementary school.…”
Section: Discussionmentioning
confidence: 99%
“…Then, Yang discussed the impact of generalpurpose e-book reading activities on English learners' English self-efficacy and language learning concepts. The survey results showed that after the e-book reading activity, the participants' overall English ability and self-confidence have been enhanced [40]. Moreover, Li has found that college students' English anxiety would be affected by internal factors to varying degrees, including self-efficacy, motivation, attribution, and business English perspectives [41].…”
Section: English Self-efficacymentioning
confidence: 99%